The Gandhian model of self-reliance in the Indian economy - Sushila Gosalia (Intereconomics, 1979)
While Mahatma Gandhi is known primarily as a freedom-fighter he had also very definite ideas on the appropriate ways of his country's economic and social development which anticipated major elements of the present development strategies of India as well as a number of other developing countries. Dr Gosalia evaluates India's revised economic strategy in order to explore the practical strength of the Gandhian model of self-reliance.
Keywords: 330; Development Strategy